Effect of the jet production on pseudorapidity, transverse momentum and transverse mass distributions of charged particles produced in pp-collisions at Tevatron energy*Supported by Higher Education Commission (HEC) Government of Pakistan under Indigenous5000 PhD Scholarship Program Batch-IV. (July 2015) - Zaman, Ali; Suleymanov, Mais; Ajaz, Muhammad; Khan, Kamal Hussain
Abstract: We investigate the effects of jet production on the following parameters: pseudorapidity, transverse momentum and transverse mass distributions of secondary charged particles produced in pp-collisions at 1.8 TeV, using the HIJING code. These distributions are analyzed for the whole range and for six selected regions of the polar angle as a function of the different number of jets. The obtained simulation results for these parameters are interpreted and discussed in connection to the increase observed in the multiplicity of secondary charged particles as a result of its multi-jet dependence, and are also discussed in comparison with the experimental results from the CDF Collaboration.